Between the Pew and the Pulpit: Can Personality Measures Help Identify Sexually Abusive Clergy?. (September 2019) - Amrom, Aria; Calkins, Cynthia; Fargo, Jamison
There has been limited conclusive research examining the personality characteristics of clergy who perpetrate abuse. To address this dearth of research, the current study aimed to develop a personality profile that distinguishes clergy members who sexually abuse children from other clergy. Personality and psychopathology were assessed using the Minnesota Multiphasic Personality Inventory–2 (MMPI-2) and the Millon Clinical Multiaxial Inventory–III (MCMI-III). Data were analyzed from a sample of clergy members, who comprised four comparison groups: clergy members referred to treatment for (a) child sexual abuse, (b) sexual misconduct with adults, (c) general clinical problems, or (d) routine employment evaluations with no previously identified clinical or sexual issues. While differences were found between groups, only the Aggressive/Sadistic scale of the MCMI-III consistently distinguished clerics who sexually abused children from all other clergy members. Findings are discussed in regard to the utility of the MMPI-2 and MCMI-III as a screening tool for clerical applicants for the Catholic Church.